Educação em tempos de pandemia: um estudo das práticas pedagógicas emergentes (2020-2021) - Werneck, Marcia Regina Garcia (2023)
This research was developed in the New Technologies in Education research line of the Postgraduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo. It aims to identify the pedagogical practices that emerged during the Covid-19 pandemic in Brazilian basic education. This study, with a quantitative-qualitative approach, consists of a systematic literature review and has as its time frame the articles, theses and dissertations published during the years 2020 and 2021, using the Capes Periodicals Portal and the Library as search sources. Brazilian Digital Theses and Dissertations (BDTD). To this end, the aim was to understand the relationships that were built between curriculum, technology and pedagogical practice. After applying the inclusion and exclusion criteria previously defined in the RSL protocol, 64 articles were selected, all submitted to the content analysis stages, with the support of Nvivo software. Of these, the focus was mainly on the anxieties, fears and desires of the period experienced, therefore, to gain a greater insight into pedagogical practices, a new analysis of 12 works was carried out. Through the inductive analysis process, the following categories emerged: 1) Collaboration and Dialogue; 2) Hybridisms; 3) Planning and Evaluation. After the analyses, it was possible to understand that, regardless of whether the class takes place in person, hybrid or online, the student's protagonism depends on the teacher's planning, and that technology is not just a means or tool to be used in education, but it It is in the culture of our society, and a paradigm shift is necessary